Factors Associated with Calcium Intake Among Third Trimester Pregnant Women in Rafsanjan City, Iran - Ebrahimi, Fatemeh (2011)
Low calcium intake is recognized as a major public health problem in vulnerable groups, especially pregnant women. Inadequate calcium intake during pregnancy can have adverse health consquences in women and infants. Thus, this crosssectional study was conducted from June 2009 to September 2009 to determine calcium intake and its associated factors among 308 pregnant women in Rafsanjan city in south east of Iran. The pregnant women were selected via purposive sampling from seven health care centres and they fulfilled the inclusion criteria of Iranian citizen, age between 18-35, in third trimester of pregnancy and have singleton pregnancy. The women were interviewed for demographic and socio-economic,obstetrical, lifestyle and dietary intake information and were measured for weight and height. The mean age of pregnant women was 26.26 ± 4.70 years and the mean years of schooling was 10.99 ± 3.15. A majority of the women (89.9%) were housewives and more than half (54.5%) were having their first pregnancy. The mean pre-pregnancy Body Mass Index (BMI) was 24.62 ± 4.05 kg/m². About 4.2% were underweight and 42.5% were overweight and obese. The mean total weight gain was 12.87 ± 3.59 kg and only 48% of the women gained weight within the recommended range. The majority of pregnant women (66.6%) had low levels of physical activity. Since all of the women were pregnant, the mean time spent for sitting was the highest(323.21 ± 122.02 min/day). The mean calorie intake was 2,271 ± 526.86 kcal/day. Most of the women (71.4%)did not meet the DRI for calcium intake in third trimester of pregnancy. In addition,a high proportion of these women did not meet the DRI for vitamin A (65.3%),vitamin D (99.1%), magnesium (82.8%), calcium (53.6%), iron (87.2%), zinc (78.9%) and folate (98.1%). The mean total calcium intake of the women was 968.51 ± 363.05 mg/day. About 84.5% of calcium was derived from food and 15.5% derived from calcium supplements. Among this sample of pregnant women, only 46.4% of the pregnant women met the DRI of 1,000 mg for calcium. Milk and dairy products (yogurt, cheese, milk, doogh, ice-cream and kashk) were made the greatest contributors to calcium intake. Cereals (bread and rice) were the most important non-dairy food sources of calcium. Comparison of socio-economic, obstetrical and lifestyle factors between pregnant women with adequate and inadequate calcium intake indicated that pregnant women with adequate calcium intake had significantly higher education (p=0.0001), household income (p=0.002), weight gain (p=0.001), energy (p=0.0001) and sodium intake (p=0.0001) and lower household size (p=0.004), gravidity (p=0.005), parity (p=0.004), number of children (p=0.004) and pre-pregnancy BMI (p=0.009) compared to pregnant women with inadequate calcium intake. Factors contributing significantly to calcium intake in pregnant women were education, household income, energy and sodium intake (R²=0.646; F=138.067, p=0.0001). Higher education, household income, energy and sodium intake were associated with higher calcium intake. The present study provided an insight into factors that contribute to calcium intake among pregnant women in Rafsanjan city. Appropriate community-based intervention programs should be developed and implemented to address inadequacy of calcium intake among pregnant women in Rafsanjan. The study finding can also be used to strengthen public health strategies that aim to improve nutritional status of pregnant women. It is also recommended that more studies be conducted in Iran to confirm the findings of this study.